Chemical coding and chemosensory properties of cholinergic brush cells in the mouse gastrointestinal and biliary tract - Schütz, Burkhard; Jurastow, Innokentij; Bader, Sandra; Ringer, Cornelia; von Engelhardt, Jakob; Chubanov, Vladimir; Gudermann, Thomas; Diener, Martin; Kummer, Wolfgang; Krasteva-Christ, Gabriela; Weihe, Eberhard (Frontiers in Physiology, 2015)
The mouse gastro-intestinal and biliary tract mucosal epithelia harbor choline acetyltransferase (ChAT)-positive brush cells with taste cell-like traits. With the aid of two transgenic mouse lines that express green fluorescent protein (EGFP) under the control of the ChAT promoter (EGFPChAT) and by using in situ hybridization and immunohistochemistry we found that EGFPChAT cells were clustered in the epithelium lining the gastric groove. EGFPChAT cells were numerous in the gall bladder and bile duct, and found scattered as solitary cells along the small and large intestine. While all EGFPChAT cells were also ChAT-positive, expression of the high-affinity choline transporter (ChT1) was never detected. Except for the proximal colon, EGFPChAT cells also lacked detectable expression of the vesicular acetylcholine transporter (VAChT). EGFPChAT cells were found to be separate from enteroendocrine cells, however they were all immunoreactive for cytokeratin 18 (CK18), transient receptor potential melastatin-like subtype 5 channel (TRPM5), and for cyclooxygenases 1 (COX1) and 2 (COX2). The ex vivo stimulation of colonic EGFPChAT cells with the bitter substance denatonium resulted in a strong increase in intracellular calcium, while in other epithelial cells such an increase was significantly weaker and also timely delayed. Subsequent stimulation with cycloheximide was ineffective in both cell populations. Given their chemical coding and chemosensory properties, EGFPChAT brush cells thus may have integrative functions and participate in induction of protective reflexes and inflammatory events by utilizing ACh and prostaglandins for paracrine signaling.